2005
DOI: 10.1007/s10582-005-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic directional structure of radiation for fields of algebraic type D

Abstract: The directional behavior of dominant components of algebraically special spin-s fields near a spacelike, timelike or null conformal infinity is studied. By extending our previous general investigations, we concentrate on fields which admit a pair of equivalent algebraically special null directions, such as the Petrov type-D gravitational fields or algebraically general electromagnetic fields. We introduce and discuss a canonical choice of the reference tetrad near infinity in all possible situations, and we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Such a tetrad is analogous to that introduced above (5.23) near a spacelike I. A detailed discussion of these tetrads and of the normalization of the field can be found in [118] (cf. also (5.36) below).…”
Section: Radiation On Timelike Imentioning
confidence: 78%
See 2 more Smart Citations
“…Such a tetrad is analogous to that introduced above (5.23) near a spacelike I. A detailed discussion of these tetrads and of the normalization of the field can be found in [118] (cf. also (5.36) below).…”
Section: Radiation On Timelike Imentioning
confidence: 78%
“…It is thus natural to choose the tetrad q ′ o , r ′ o , s ′ o adapted to them: we require that one (double degenerate) PND has inclination θ s with respect to q ′ o , the second PND has the same inclination with respect to −q ′ o (i.e. θ s = (π − θ 1 )/2), and that the vector s ′ o is perpendicular to the plane spanned by these PNDs (see [118] for more details). With respect to this reference tetrad the PNDs are parameterized by the coefficients R 1 = R 2 = tan θs 2 and R 3 = R 4 = cot θs 2 .…”
Section: Radiation On Spacelike Imentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we analyze the directional structure at conformal infinity of the leading component of the field which corresponds to radiation. In fact, this is a natural extension of our previous work [9][10][11][12] in which we completely described the asymptotic directional structure of radiation in four-dimensional spacetimes with conformal infinity of any character (null, spacelike, or timelike). We demonstrated that this directional structure has universal properties that are basically given by the algebraic type of given spacetime, namely the degeneracy and orientation of principal null directions of the Weyl tensor.…”
Section: Introductionmentioning
confidence: 67%
“…It was recently demonstrated in the series of papers [4][5][6][7][8][9][10][11] that such a directional structure of gravitational or electromagnetic radiation can be generally described in a closed form. In fact, it has a universal character that is essentially determined by the algebraic type of the given field, namely by local degeneracy and orientation of its principal null directions on I.…”
Section: Introductionmentioning
confidence: 99%